Diurnal variation of particle-bound PAHs in an urban area of Spain using TD-GC/MS: Influence of meteorological parameters and emission sources. (August 2016) - Elorduy, I.; Elcoroaristizabal, S.; Durana, N.; García, J.A.; Alonso, L.
Abstract: Short –term particulate concentrations of 13 polycyclic aromatic hydrocarbons (PAHs) in PM10 were determined in the urban area of Bilbao (Spain). The analysis was performed by thermal desorption coupled with gas chromatography-mass spectrometry (TD-GC/MS), which enabled to use three diurnal periods of 8 h sampling basis time resolution. A total of 105 PM10 samples were collected during 5 months in 2013. Diurnal average concentration of total PAHs (∑13 PAHs) ranged from 1.18 to 9.78 ng m −3 ; and from 0.06 to 0.70 ng m −3 for benzo[ a ]pyrene. The presence of high concentrations of benzo[ b ]fluoranthene, pyrene, fluoranthene and chrysene, and the significant PAHs diurnal variations due to the sampling period, pointed out the influence of mixing anthropogenic sources and meteorological conditions. The diurnal pattern of source contributions was assessed by binary diagnostic ratios and principal component analysis (PCA). These results showed the prevalence of pyrogenic sources coming from traffic and coal/coke combustion sources. Moreover, the PCA differentiated a diurnal pattern of source contributions. The influence of meteorological factors was studied by Pearson correlation analysis and multiple linear regression. Three factors, temperature, wind speed and atmospheric pressure, were identified as the most significant ones affecting diurnal PAHs concentrations. Finally, PCA of the PAHs levels, regulated atmospheric pollutants and meteorological parameters showed that diurnal PAHs concentrations were mainly influenced by variations in the emission sources, atmospheric oxidants such as ozone, and temperature conditions. These results provide further insight into the PAHs diurnal patterns in urban areas by using higher temporal resolutions. Highlights: Short-term data analysis of 13 PM10 –bound PAHs pointed out different diurnal patterns. BbFt, Pyr, Ft and Chry were the major contributors to total PAHs in PM10 . Traffic and industrial sources influenced PAHs diurnal variability. The most influential meteorological factors were temperature, wind speed and pressure. Ozone was one of the main controlling factors except during the night time.